2016
DOI: 10.1021/acsbiomaterials.6b00167
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Neurotrophin-3 Treatment in an Injectable Collagen Scaffold Following Rat Spinal Cord Hemisection Injury

Abstract: Background. Spinal cord injury (SCI) presents to the clinic as complete, incomplete or compressive. SCI patients also display varying quantities of spinal cord tissue damage or loss. One theory proposed to repair the injured spinal cord and regain motor control is to regenerate axons through the lesion site. Current methods proposed to increase neuroregeneration following SCI include; preserving spared neuronal tissue, increasing axonal regeneration, reducing inflammation, reducing glial scar formation and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 69 publications
0
28
0
Order By: Relevance
“… 30 A previous study by our group demonstrated that collagen hydrogel reduced the amount of ionized calcium-binding adaptor molecule 1 (Iba-1) and neuron-glial antigen 2 (NG2) chondroitin sulfate proteoglycan (CSPG)-positive staining and led to improved motor function following SCI. 31 Considering these observed effects, we asked whether the glycosylation profile of the tissue may also be influenced by treatment with a biomaterial. From recent in vitro studies, it is clear that coupling glycans and collagen can influence populations of neural cells: either by driving neuronal differentiation of immortalized cell lines 32 or by influencing the glycosylation status of primary neural cells, 33 and this strategy will warrant investigation in SCI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 A previous study by our group demonstrated that collagen hydrogel reduced the amount of ionized calcium-binding adaptor molecule 1 (Iba-1) and neuron-glial antigen 2 (NG2) chondroitin sulfate proteoglycan (CSPG)-positive staining and led to improved motor function following SCI. 31 Considering these observed effects, we asked whether the glycosylation profile of the tissue may also be influenced by treatment with a biomaterial. From recent in vitro studies, it is clear that coupling glycans and collagen can influence populations of neural cells: either by driving neuronal differentiation of immortalized cell lines 32 or by influencing the glycosylation status of primary neural cells, 33 and this strategy will warrant investigation in SCI.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we use a collagen hydrogel for the treatment of SCI in the rat. Although collagen is a minor constituent of the CNS extracellular matrix, 34 it is well tolerated, not eliciting any obvious foreign body response, 31 , 35 , 36 and has been approved by FDA for peripheral nerve treatments. 37 Being a fibrillar protein, collagen can be manipulated to provide aligned surface guidance for migrating cells or growing axons.…”
Section: Introductionmentioning
confidence: 99%
“…NTF-3 is the gene that encodes the NT-3 protein [8], and function as a neurotrophic factor that is responsible for enhancing the development of neuron function [9]. The NT-3 protein can increase the regeneration of damaged neurons by binding to the ERBb gene [10]. The NT-3 protein plays an important role in controlling the number of neurons and the growth of dendrites [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the great potential of collagen-based scaffolds as cell carriers and bridging material in numerous experimental animal models of CNS. The implantation has been demonstrated to be safe and has induced significant repair in SCI by increasing neurons and inhibiting glial scar formation [ 27 , 28 , 29 ]. Hence, collagen has become one of the most favored natural material sources for treating SCI.…”
Section: Introductionmentioning
confidence: 99%